Control of poly(A) tail metabolism during inducible gene expression - Parker, Hannah (2016)
In gene regulation, mRNA polyadenylation, deadenylation and decay are closely linked processes whose full biological importance is only starting to emerge. Using thiouridine labelling as a method of capturing newly synthesised mRNAs, we have been able to measure poly(A) tail sizes of newly synthesised individual and total mRNAs in mouse NIH3T3 cells and global changes in mRNA turnover during the loss of pluripotency in human embryonic stem cells. These two systems, although very different, allow us to study changes in individual mRNAs during inducible gene expression. In order to track changes of poly(A) tail length during rapid gene induction we have used the serum response as a model in NIH 3T3 cells. Using poly(A) fractionation technique (Meijer et al, 2007), we have been able to study global changes of the poly(A) tail length during the serum response and have observed striking increases in rapidly induced mRNAs compared to control levels. Functional analysis reveals that these mRNAs are involved in transcriptional regulation, indicating that they are involved in reprogramming gene expression. Further analysis of the poly(A) fractionation microarray data, also indicates that certain mRNAs, such as Akt2, change in poly(A) tail length but are either down regulated of have no change in abundance. This group of genes areis enriched in regulators of signal transduction. When treated with Actinomycin D, some of these mRNAs still retain the increased poly(A) tail length during the serum response. This suggests a role for cytoplasmic polyadenylation, as inhibiting transcription has no effect on the elongation of the poly(A) tail. We also established by Western blotting and immunohistochemistry, that despite reduced mRNA levels, protein levels of Akt2 increase during the serum response. We conducted microarray analysis to determine whether miRNA regulation contributes to the changes we observed in poly(A) tails during the serum response. However, no major changes in abundance are found after 30 minute treatment, indicating that all changes in microRNA abundance are slow and unlikely to play a role in this system. As a second system, we studied the role of RNA binding proteins and mRNA stability in the early neuronal differentiation of human pluripotent stem cells, when pluripotency is lost. The role of mRNA processing and stability on the maintenance and establishment of pluripotency is poorly studied, despite the fact that these processes are important in germline development and early embryogenesis. We therefore studied the differential expression of RNA binding proteins involved in the regulation of polyadenylation and mRNA stability during early differentiation of human embryonic stem cells into neuronal precursors. Over an 8 day time period we have found large changes in mRNAs belonging to the CELF, CPEB, PUM and MSI families, which start early after the indication of differentiation, when pluripotency is lost. Using thiouridine labelling and microarray analysis on differentiating and pluripotent cells we were able to identify a group of mRNAs which appear to be destabilised during differentiation. This group includes known pluripotency factors such as OCT4 and LIN28B. Functional analysis showed that many ribosomal protein mRNAs also are within this group and also genes involved in the regulation of translation elongation, further exposing an important role for post-transcriptional regulation in the maintenance and loss of pluripotency. Our data indicate that the initial poly(A) tail size and mRNA turnover rate can vary greatly depending on both the individual mRNA and the state of the cell. Overall, our investigations give intriguing glimpses in the role of poly(A) tail metabolism and mRNA stability in two different models of inducible gene expression.